Staphylococcus aureus food poisoning among Bulawayo City Council employees, Zimbabwe, 2014. (December 2015) - Gumbo, Amen; Bangure, Donewell; Gombe, Notion; Mungati, More; Tshimanga, Mufuta; Hwalima, Zanele; Dube, Ignatious
Abstract Background Bulawayo City Council held an Integrated Result Based Management workshop among 86 employees from August 18–22, 2014 at Ikhwezi Training Centre in Bulawayo City. On August 21, 2014, a report of diarrhoea among Council employees attending the workshop was received. We investigated the outbreak to determine the risk factors associated with diarrhoea at Ikhwezi Training Centre, Bulawayo City. Method A retrospective cohort study was conducted where 74 Council employees were interviewed on food consumed and presenting signs and symptoms. Stool specimens and hand swabs were collected for culture. Water samples were collected for bacteriological analysis. Food samples were not available. Data were analysed using Epi Info™ to generate frequencies, means, proportions, risk ratios, and attributable risk. Results Of the 74 employees interviewed 34 (45.9 %) were males and 40 (54 %) were females. The response rate was 94 %. The common signs and symptoms included abdominal cramps (88.7 %), and watery diarrhoea (86.8 %). The overall attack rate was 71.6 %. Eating stewed chicken (RR = 2.52, 95 % CI 1.30–4.89) served at hour 13:00 during lunch on August 20, 2014 at Ikhwezi Training Centre was the only significant risk factor associated with food poisoning. Drinking purified bottled water [RR = 0.67, 95 % CI (0.57–0.79)] was found to be protective. Staphylococcus aureus was isolated from the hands and nails of food handlers. Conclusion The outbreak was due to food poisoning and was most likely caused by the Staphylococcus aureus formed toxins. Stewed chicken served during lunch on August 20, 2014 was the possible source of infection. Contamination might have occurred during food handling and preparation. Training of food handlers in basic food hygiene and safety is recommended.